PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN ROKOK GUDANG GARAM PADA TOKO AZIZ PUTRA MANGUNSAREN - Pujiastuti, Endah; Kusumaningati, Iip Dyah; Faisal, Muhmmad Mahfudz (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This study aims to determine the effect of brand image on decision to buy Gudang Garam cigarettes at Aziz Putra Mangunsaren Store. The research method used in this study is the research method quantitatively by using a sample of 100 consumers of Toko Aziz Putra Mangunsaren. Sampling using judgmental sampling. Method data analysis used in this research is descriptive analysis method and simple linear regression analysis. Data processing is done by using computer software program SPSS 25. The results of this study shows that brand image has a positive and significant effect on decision to buy Gudang Garam cigarettes at Aziz Putra Mangunsaren Stor